Does Remittance Income Spur Food Imports? Evidence from a Developing Country: Array - Megbowon, Ebenezer; Sanusi, Gbenga (Acta Universitatis Danubius. Œconomica, 2020)
As a source of foreign earning, remittance income has been considered to be a financial resource which could be utilized to pursue economic development goals. This study therefore examines the effectiveness of remittance income on food importation in Nigeria using time-series data for the period 1977 to 2019. The study employed the auto-regressive distributed lag (ARDL) estimation technique to achieve the aim of the study. Results from the analyses indicates that remittance income have negative impact on food importation in both the short-run and long-run. We therefore conclude that remittance inflows do not play a crucial role in increasing food import. Nigeria can benefit from it by investing remittance in productive investment that will have a positive effect on domestic agricultural productivity. Additionally, policy that discourages food importation in the favour of domestic agricultural production should be promoted. This include ban or increase tax of selected food import where the country does not have an absolute advantage and depreciation of real effective exchange rate.